2006
DOI: 10.1302/0301-620x.88b1.16600
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the shrinkage of commercial bone cements when mixed under vacuum

Abstract: The outcome of a cemented hip arthroplasty is partly dependent on the type of cement which is used. The production of an interface gap between the stem and the cement mantle as a result of shrinkage of the cement, may be a factor involved. Palacos R, Palacos LV (both with gentamicin), CMW 1, CMW 2, CMW Endurance (CMWE) and Simplex were prepared under vacuum and allowed to cure overnight in similar cylinders. The next day this volume was determined by the displacement of water. Shrinkage varied between 3.82% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…This expansion is in contrast to the small contraction of the PMMA cement during cure. 16 An additional factor in the elevated strength might relate to a potential modulus-related reduction in stress concentrations in specimens fixed with PBC versus PMMA. Future material-specific finite element modeling might provide insight into this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This expansion is in contrast to the small contraction of the PMMA cement during cure. 16 An additional factor in the elevated strength might relate to a potential modulus-related reduction in stress concentrations in specimens fixed with PBC versus PMMA. Future material-specific finite element modeling might provide insight into this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PMMA volumetrically contracts during curing, increasing the likelihood for gap formation at the interface of cement to trabecular bone. 16 Similarly, a severe material property mismatch between cancellous bone (modulus generally in the 50 -500 MPa range 17 ) and rigid PMMA (modulus of approximately 2500 -3000 MPa 18 ) increases the potential for stress shielding, bone resorption, and fracture at the cement-bone interface. Polymethylmethacrylate fails to integrate with host bone, lacking the porosity requisite for bone ingrowth into the material.…”
mentioning
confidence: 99%
“…The statistical differences found in our study must be considered irrelevant, as much higher shrinkage values are commonly found. If they had been vacuum-mixed, thus reducing the porosity of the cement, we would have expected up to 7% shrinkage (Kwong and Power 2006).…”
Section: Discussionmentioning
confidence: 99%
“…[14] Silorane-based composite has the advantage of low shrinkage (0.79%) compared with several commercial PMMA cements (3.82-7.08%). [15] The results of bond strength tests usually have a wide variation. Researchers often present data using mean value and standard deviation.…”
Section: Discussionmentioning
confidence: 99%